Local Government Financial Performance: The Role of Political Monitoring - Putri, Miranti; Aswar, Khoirul (Journal of Economics and Behavioral Studies, 2022)
This study intends to investigate and demonstrate the impact of local government financial performance as influenced by political oversight, regional wealth, intergovernmental revenue, and capital spending. In Indonesia in 2019, the district/city local governments were the subject of this study. The Report on Local Government Finances (LKPD) accessible at the Audit Board of the Republic of Indonesia was used as secondary data (BPK RI). The data used in this study included 491 data samples chosen using the purposive selection approach from 507 districts/cities across Indonesia. The analytical method used in this study was path analysis with Smart PLS software and a significance level of 5%. Structural Equation Modeling was used for data analysis (SEM). The findings of this investigation showed that regional wealth, intergovernmental revenue, and capital expenditures have an impact on local government’s financial performance. Political supervision, however, does not mitigate the association between intergovernmental revenues and capital expenditures on the financial performance of local governments, which reduces the relationship between regional wealth and local government financial performance. The results of this study are anticipated to be used as source material for studies on the factors affecting local government financial performance and to help local governments by providing information on the monitoring activities carried out by numerous Regional People’s Representative Council (DPRD) members. As a result, local governments will be encouraged to increase legislative oversight to improve their financial performance.